The burden of hypercholesterolemia and ischemic heart disease in an ageing world - Angela Pirillo; Giuseppe Danilo Norata (Elsevier, 2023)
Despite a general improvement in global health conditions in the last decades, cardiovascular diseases (CVDs) are still the first global cause of death and disability worldwide, with ischemic heart disease (IHD) being responsible for half of CVD deaths. Hypercholesterolemia is a major causal risk factor for IHD. Although the availability of effective cholesterol-lowering drugs largely increased in the last few years, we are still facing disparities in the awareness of dyslipidaemia as a CVD-associated risk factor and therefore in health expenditure among different world areas. Although no significant changes have been reported globally in the levels of plasma cholesterol in the last three decades, relevant differences among world areas according to their economic status can be observed. Only high-income countries have experienced an improvement in plasma lipid profile which translated into a substantial decrease in the deaths and disabilities due to IHD, whereas countries in other income groups showed no reduction or even an increase. As expected, most of the deaths for IHD attributable to high LDL-C occur in people aged 60 years and above, although significant differences can be observed according to income. Altogether these observations suggest the need for measures to reduce the gap in treating hypercholesterolemia among income groups, with special attention to women and older people.